Do Individuals Put Effort into Lying? Evidence From a Compliance Experiment - Tim Lohse; Nadja Dwenger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study whether individuals in a face-to-face situation can successfully exert some lying effort to delude others. We exploit data from a laboratory experiment in which participants were asked to assess videotaped statements as being rather truthful or untruthful. The statements are face-to-face tax declarations which were recorded in an incentivised tax compliance experiment. The video clips to be assessed feature each subject twice making the same declaration. But one time the subject is reporting truthfully, the other time willingly untruthfully. This allows us to investigate within-subject differences in trustworthiness. Drawing on more than 18,000 assessments, we find that a subject is perceived as more trustworthy if she deceives than if she reports truthfully. It is particularily individuals with dishonest appearance who manage to increase their perceived trustworthiness by up to 15 percent. This is evidence of individuals successfully exerting lying effort.
Keywords: C91; H31; K42; 330